2010
DOI: 10.14411/eje.2010.012
|View full text |Cite
|
Sign up to set email alerts
|

Species coexistence patterns in a mycophagous insect community inhabiting the wood-decaying bracket fungus Cryptoporus volvatus (Polyporaceae: Basidiomycota)

Abstract: Abstract.A study of the insect community inhabiting the wood-decaying bracket fungus, Cryptoporus volvatus was used to test two hypotheses proposed to account for the competitive coexistence of species in insect communities in patchy environments, niche partitioning and spatial mechanisms. A total of 8990 individuals belonging to 17 insect species emerged from 438 sporocarps (patches) collected from the field. Insect species richness increased and then declined with increase in the total insect biomass reared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…25 on 19 May. This temporal pattern qualitatively matches with the phenology of the two beetles revealed by sampling from multiple C. volvatus ‐infested trees (adults Setsuda 1995; larvae Kadowaki 2010). However, Setsuda (1995) revealed a large overlapping pattern in seasonal occurrence between the two tenebrionids.…”
supporting
confidence: 76%
“…25 on 19 May. This temporal pattern qualitatively matches with the phenology of the two beetles revealed by sampling from multiple C. volvatus ‐infested trees (adults Setsuda 1995; larvae Kadowaki 2010). However, Setsuda (1995) revealed a large overlapping pattern in seasonal occurrence between the two tenebrionids.…”
supporting
confidence: 76%
“…Ranius et al 2005), associations with specific fungi may play an important role in the selection of appropriate microhabitats, as has been observed in many saproxylic beetles (Kaila et al 1994;Leather et al 2013). Interspecific competition is considered one of the most important factors affecting populations of insects inhabiting the same niches (Coulson et al 1976;Denno et al 1995;Kadowaki 2010;Weslien et al 2011), therefore it should be expected also in the case of hollow-dwelling species. Unexpectedly, we were unable to reveal an influence of co-occurring cetoniid larvae on the survival of O. barnabita larvae, although both taxa have similar microhabitats requirements.…”
Section: Discussionmentioning
confidence: 96%
“…have demonstrated that spatial aggregative responses are a key mechanism regulating their diversity in the patchy environment (e.g., Atkinson and Shorrocks 1984, Wertheim et al 2000, Inouye 2005, Takahashi 2006, Kadowaki 2010, Fader and Juliano 2013. Theory predicts that when resource clumps are sparsely distributed (entailing high travel costs), it would be adaptive for females to produce fewer, larger clutches because they have fewer chances to encounter resource clumps (Heard and Remer 1997).…”
Section: Discussionmentioning
confidence: 99%